Effect of antenatal care and social well-being on early neonatal mortality in Bangladesh - Sanjit Roy; Md. Aminul Haque (BMC, 2018)
Abstract Background Bangladesh has achieved MDG 4, but although post neonatal and child mortality have shown impressive declines, neonatal mortality is still lagging behind. More efforts have to be made to improve this state of affairs. The objective of this paper is to identify the effect of proper antenatal care and social wellbeing on early neonatal mortality in Bangladesh. Methods The data used for this study is the Bangladesh Multiple Indicator Cluster Survey. This study used several independent variables such as mother's school attendance, receiving antenatal care, receiving TT injection, place of residence and wealth quintile. Here both bivariate and multivariate analysis have been used. At bivariate level, simple cross tabulation and appropriate measures of association have been used to find out the statistical association between dependent and independent variables. In this study the outcome/dependent variable is early neonatal mortality (children who died within 7 days after birth) which is a binary variable. If early neonatal mortality occurs among the respondents then it is considered as 1, otherwise it is considered as 0. Logistic regression was used to identify the factors which are involved in reducing this early neonatal mortality. Results Women who received antenatal care during their time of pregnancy are likely to have 18% lower odds of experiencing early neonatal mortality (OR = 0.82, CI = (0.71-0.95)) compared to groups who did not receive antenatal care during pregnancy. In terms of social well-being, the woman who comes from the richest family are likely to have 45% lower odds of experiencing early neonatal mortality (OR = 0.55, CI = (0.42-0.720) compared to the poorest one. Conclusion The outcomes of this paper suggest that the women's antenatal care and social well-being has a significant effect on early neonatal mortality.